Application of a kiln drying technique to Quercus suber L. cork planks - Carpintero, E.; Jurado, M.; Prades, C. (Food and Bioproducts Processing, 2014)
At present, all of the cork used to manufacture natural stoppers is air dried for a minimum of 6 months. This study evaluates the feasibility of applying a kiln drying technique to cork planks. We used a sample of 65 planks, each of which was divided into two pieces. One sub-set of planks was air dried for 6 months following the traditional procedure, while the other was kiln dried for 14 days. The evolution of moisture content was controlled, and both methods were compared by means of a statistical analysis of the thickness, quality, porosity coefficient, color and compressive properties of the cork. The reduction in moisture content was similar for both traditional air drying and kiln drying. At the end of the drying, cork thickness increased with both methods, although a larger increase was observed for the kiln drying method. Statistically significant differences were not found for the mean porosity coefficient or quality. Although statistically significant differences in the color of the cork were detected, it would be necessary to verify if such differences are detectable by the human eye. No differences were found in the compressive properties of the cork for a significance level of less than 1%. This feasibility study concludes that kiln drying is a suitable technique as it significantly reduces the drying time and holding costs of the raw material. The application of this technique would constitute an innovation in the transformation process by controlling the climatic variables that affect the drying process.
Keywords: Compressive properties; Kiln drying; Moisture content; Quality; Thickness; Traditional air drying

Drying kinetics of cork planks in a cork pile in the field - Costa, Augusta; Pereira, Helena (Food and Bioproducts Processing, 2012)
Moisture content is one important parameter in the trading of raw cork planks after harvesting. This study presents a mathematical modeling of the drying curve of raw cork planks in a cork pile in the ﬁeld, under natural sun drying conditions. Experimental data were obtained by following the water loss (i.e. by daily weighing) of 97 cork planks positioned in nine points within a cork pile. Immediately after harvesting, the raw cork planks had a mean moisture content in a dry basis of 40.4% and after 20-day drying 16.6%. The drying process of the cork planks showed three phases: drying was very fast in the ﬁrst 2 days; in the next 2–15 days there was a decreasing drying rate; and a ﬁnal phase, after 15 days in the cork pile, with a slightly decreasing drying rate. Mathematical modeling provided a direct relation between moisture content and drying time. After comparing sixteen empirical drying models, the Modiﬁed Henderson and Pabis model showed the best ﬁt. According to this model, the cork planks are commercial dry (14% moisture content in a wet basis) 15 days after harvest.
The following values have no corresponding Zotero field: publisher: Institution of Chemical Engineers
Keywords: Cork; empirical drying models; Moisture content; moisture ratio; natural sun drying

A Simple Technique to Estimate the Flammability Index of Moroccan Forest Fuels - Hachmi, M'Hamed; Sesbou, Abdessadek; Benjelloun, Hassan; El Handouz, Nesrine; Bouanane, Fadoua (Journal of Combustion, 2011)
A formula to estimate forest fuel flammability index (FI) is proposed, integrating three species flammability parameters: time to ignition, time of combustion, and flame height. Thirty-one (31)Moroccan tree and shrub species were tested within a wide range of fuel moisture contents. Six species flammability classes were identified. An ANOVA of the FI-values was performed and analyzed using four different sample sizes of 12, 24, 36, and 50 flammability tests. Fuel humidity content is inversely correlated to the FI-value, and the linear model appears to be the most adequate equation that may predict the hypothetical threshold-point of humidity of extinction. Most of the Moroccan forest fuels studied are classified as moderately flammable to flammable species based on their average humidity content, calculated for the summer period from July to September.
Keywords: flammability; forest species; Moisture content; Morocco (voyant)

Comportement physiologique des glands de chêne liège (Quercus suber L.) durant leur conservation et variabilité inter-individus producteurs - Merouani, Hachemi; Branco, Carmen; Almeida, Maria Helena; Pereira, João S. (Ann. For. Sci., 2001)
The mature acorns were harvested on twelve selected trees from a cork oak population in Southern Portugal (Herdade da Palma). After drying, the seed lots were stored on three types bags (polyethylene with 30 mm and 50 mm thick and plastic mesh), for six months at 0 oC. At the time of natural dissemination, the acorns from the majority of the trees from the same population were under the same state of morphological and physiological maturity. The moisture content was about 44-47% and a germination rate above 92% . At this time, the germination was very slow because of the existent embryonic dormancy that seems to be dependent on the individual trees. During the storage, germination rate is improved. This might be explained by the breaking dormancy during storage. The mean germination time was on an average 10 days for fresh seeds and decreased to about 4 days after 6 months storage. A relationship between viability and seed moisture content was observed. The Mean Germination Time of dried seed and stored seed for 4 months in plastic mesh bag increased to about 13 days. The germination capacity was strongly decreased when the seed moisture content was below 30%
Keywords: electrolyte leakage; germination; Moisture content; Quercus suber; seed; storage